2020
DOI: 10.1002/chem.202003067
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Water in the Mechanosynthesis of CsPbI3 and Other ABX3 Halides

Abstract: Mechanochemical synthesis of CsPbI 3 ,a sa model system for ABX 3 halides, was studied.W ater was shown to strongly promote the kinetics of formation of CsPbI 3 from the CsI + PbI 2 mixture through increased mobility of the constituting ionic species.S ince many binary and ternary halides are hygroscopic, it was concluded that the presence of small, uncontrollable and unintentional additions of water should often occur in both precursor mixtures and synthesized complex halides boostingthe kinetics of formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[99] Moreover, in situ released liquid products in mechanochemical transformations have been observed to accelerate chemical reactions, [100] thus indicating the possibility for LAG catalysis (Figure 4c). [101] Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols. [102][103][104][105] But not only liquids have been used as auxiliaries in ball milling reactions, the addition of catalytic amounts of solid ionic salts has also been a common practice.…”
Section: Gc 5: Safer Solvents and Auxiliariesmentioning
confidence: 99%
See 1 more Smart Citation
“…[99] Moreover, in situ released liquid products in mechanochemical transformations have been observed to accelerate chemical reactions, [100] thus indicating the possibility for LAG catalysis (Figure 4c). [101] Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols. [102][103][104][105] But not only liquids have been used as auxiliaries in ball milling reactions, the addition of catalytic amounts of solid ionic salts has also been a common practice.…”
Section: Gc 5: Safer Solvents and Auxiliariesmentioning
confidence: 99%
“…Additionally, it has been reported that LAG can exert inhibitive or prohibitive effects on the formation of molecular crystals by mechanochemistry [99] . Moreover, in situ released liquid products in mechanochemical transformations have been observed to accelerate chemical reactions, [100] thus indicating the possibility for LAG catalysis (Figure 4c) [101] . Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols [102–105] …”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%